Marriage Perception Towards Ria Ricis Divorce News on @Lambe_turah - Nindia, Mesy Rino; Salsabilla, Annisya; Putri, Yulia Eka; Salindeho, Arnetta Ayu Carolina (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This research investigates public opinion on the divorce of social media celebrity Ria Ricis, utilizing Sara Mills' Critical Discourse Analysis (CDA) framework to explore the discourse surrounding this event on social media. Ria Ricis, widely recognized for her YouTube presence, and her marriage to Teuku Ryan attracted significant attention, with their subsequent divorce sparking extensive reactions on social media, particularly on the popular Instagram account @lambe_turah. The study analyzes the subject-object positions in the discourse, revealing the power dynamics and ideological content embedded within the narrative. Drawing on previous studies that employed Mills’ CDA framework, this research aims to uncover how public figures' personal lives are constructed and interpreted in social media discourse, and how these representations reflect broader societal attitudes towards celebrity relationships and authenticity on social media platforms.